Modeling of the conductivity in electrolytes based H2SO4- Cu - Cifuentes, Gerardo (2010)
For different sulfuric acid and copper base electrolyte, have studied the properties of electrical conductivity in concentrated solutions of these studies have derived expressions (mathematical models) that can theoretically relate the behaviour of conductivity with respect to other properties of the solution, such as concentration, diffusivity and its dependence on temperature and other properties of the system